Analgesic Profile in Intensive Observation Room (Ruang Observasi Intensif/ ROI) Dr. Soetomo General Hospital Surabaya - Bunga Priscilla Rotua Manurung; Maulydia Maulydia; Maftuchah Rochmanti; Nancy Margarita Rehatta (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif, 2023)
Introduction: Pain is a condition that the majority of critical care patients will possibly suffer at some point during their stay in the intensive care unti (ICU). In both medical and surgical ICU patients, the incidence of considerable pain is still 50% or greater. Analgesic administration is considered one of the most effective pain managements. While useful, it can cause detrimental effects if not used according to its indications and regulations.Objective: To obtain the analgesic profile used in intensive observation room (ruang observasi intensif/ROI) Dr. Soetomo General Hospital Surabaya.Methods: This study is a retrospective descriptive study with 537 medical records met the inclusion criteria.Result: The most frequent analgesic used is metamizole (44.41%) and paracetamol (16.08%) while ketamine was used the least (0.24%). Most commonly used analgesic adjuvants is phenytoin (6.12%). The amount of single drug administration (52.70%) is more frequent than multimodal analgesic (47.30%). Metamizole with paracetamol is the most popular analgesic combination (20.74%), followed by metamizole with tramadol (14.17%), and metamizole with fentanyl (12.99%). The most common procedures recorded are obstetrics and gynaecological (29.98%), cranial and general surgery with the same result (21.42%), and orthopaedic (12.29%). 205 samples with Wong-Baker FACES Pain Ratings Scales stated that there is an increase in patients who do not experience pain after administration of analgesics (N=25 to N=132), patients that underwent mild pain decreased (N=134 to N=65), and patients with moderate and severe pain also decreased (N=43 to N=8 and N=3 to N=0 respectively).Conclusion: Non-opioid analgesic dominates the analgesic profile in ROI Dr. Soetomo General Hospital Surabaya compared to opioids that generally used the most worldwide. Giving analgesics to patients has been proven successful in reducing the pain degree.